A REVIEW OF RAILWAY TRACKS MAINTENANCE OPTIMIZATION THROUGH RAMS METHOD - Hadi, Rasyadani Luthfan; Wicaksono, Satrio; Suweca , I Wayan (Jurnal Rekayasa Mesin, 2025)
Railway tracks are complex assets that require a comprehensive and integrated management approach to improve service quality in the era of modernization of the railway industry. The RAMS (Reliability, Availability, Maintainability, and Safety) method is one of the approaches used in managing railway track to ensure that the railway system operates safely. The discussion in this literature review is categorized into three sections including (1) RAMS on Railway Tracks, (2) RAMS Analysis Tools on Railway Tracks such as RBD, FMEA, FMECA, and FTA, then, (3) Challenges and Future Directions of RAMS on Railway Tracks. Based on the review, research related to RAMS in railway tracks is limited due to the complexity of the railway tracks. However, the formulations and principles of research associated with RAMS on railway systems can be adopted in the analysis of RAMS railway tracks because the principles generally apply to railway systems including railway tracks. The implementation of RAMS on railway tracks can be used as a reference to improve the performance of railway track assets and provide long-term benefits by minimizing costs due to accidents or catastrophic failures for the Indonesian railway industry.